2021
DOI: 10.4038/jnsfsr.v49i3.10305
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro culture of Nymphaea nouchali seeds; a conservation approach for a vulnerable species

Abstract: Nymphaea nouchali var. nouchali is a nonviviparous species with a slow natural propagation by rhizomes or seeds. The plant is threatened in its natural habitats due to several reasons and is included in the vulnerable category of the National Red List of Sri Lanka. In vitro contamination-free culture method was developed to initiate mass propagation of the species. Results were validated through molecular and microscopic studies. Bacterial growth occurred in the seeds disinfected via the standard method using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…with sterilized distilled water, seeds were subject to further sterilization with 70% ethanol for 2 min. Additional step of treating the seeds with 25% sulphuric acid (Perera et al 2021) was included for the varieties that showed continuous contamination. Finally, seeds were thoroughly rinsed with sterilized distilled water for three times each with 2 min agitation.…”
Section: Preparation Of Plant Materialsmentioning
confidence: 99%
“…with sterilized distilled water, seeds were subject to further sterilization with 70% ethanol for 2 min. Additional step of treating the seeds with 25% sulphuric acid (Perera et al 2021) was included for the varieties that showed continuous contamination. Finally, seeds were thoroughly rinsed with sterilized distilled water for three times each with 2 min agitation.…”
Section: Preparation Of Plant Materialsmentioning
confidence: 99%